Gender issues in caring for demented relatives - Papastavrou, Evridiki; Tsangari, Haritini; Kalokerinou, Athena; Papacostas, Savvas S.; Sourtzi, Panagiota (My University, 2009)
Background:The burden of providing care for dementia patients falls increasingly upon families and it has been identified as a chronic stressor that places family members at risk for physical and emotional problems. Aims: To explore family burden in the care of patients with dementia in Cyprus and to look at gender differences in the area of caregiving and its consequences like burden, psychiatric morbidity and coping with caregiving difficulties. Methods:This is a cross-sectional study, with a sample of 172 primary caregivers. The questionnaire included the Memory and Behavior Problem Checklist, the Zarit Burden Interview, the Center of Epidemiological Studies Depression scale, and the Ways of Coping Questionnaire. Several statistical methods were used for data analysis, such as independent samples t-tests. One-way ANOVA, chi-square tests of independence, reliability studies and factor analysis. Results:The analysis revealed gender differences in the overall burden (p-value=0.048) and depression (p-value=0.011) where female caregivers experience higher levels compared to males. Women had a higher mean of burden in the questions included in relational deprivation (10.44 compared to 8.47 for men) and this difference is statistically significant (p=0.02). Oneway ANOVA showed that, according to kinship, there exist some highly significant differences in burden (F=6.17, p=0.003) and marginal differences in depression (F=2.74, p=0.067) with the sons being less affected by the consequences of caregiving. Regarding the ways of coping, women use mostly emotional-focused strategies like denial (p =0.09). Conclusions: The results of this study confirm gender differences for dementia family caregivers as regards burden and depression. The study clearly indicates the need for programs to help relieve the vulnerable caregivers especially in the area of coping so to alleviate the harmful effects of caregiving.
Keywords: Burden; Caregiving; Coping; Dementia; Gender